Measurements of W and Z boson production in ATLAS - Zhibo Wu (SciPost Physics Proceedings, 2022)
Precision measurements of the production cross-sections of W and Z boson at LHC provide important tests of perturbative QCD and information about the parton distribution functions for quarks within the proton. We present measurements of cross sections for inclusive $W^+$, $W^{-}$ and Z boson production using data collected by the ATLAS experiment at a center-of-mass energy of $\sqrt{s}$=2.76 TeV. Measurement of the transverse momentum distribution of Z boson at $\sqrt{s}$=13 TeV is also presented. The measurements are corrected for detector effects and compared with state-of-the-art theoretical calculations.